2020
DOI: 10.47162/rjme.61.2.20
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-invasive scores in determining the liver fibrosis in NAFLD and psoriatic patients

Abstract: This is an open-access article distributed under the terms of a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International Public License, which permits unrestricted use, adaptation, distribution and reproduction in any medium, non-commercially, provided the new creations are licensed under identical terms as the original work and the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Molecular studies have provided important insights into the pathogenesis of this relatively common condition. One of the most important advances has been the identification of the links between obesity, insulin resistance, inflammation and NAFLD [ 20 , 21 ]. Data from the literature have shown that insulin resistance and its hepatic consequence, NAFLD, could be the result of widespread inflammation [ 22 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Molecular studies have provided important insights into the pathogenesis of this relatively common condition. One of the most important advances has been the identification of the links between obesity, insulin resistance, inflammation and NAFLD [ 20 , 21 ]. Data from the literature have shown that insulin resistance and its hepatic consequence, NAFLD, could be the result of widespread inflammation [ 22 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…In general, ALT and AST values are not much higher than the reference values (on average, 2–3 times the threshold value), with an ALT–AST ratio above one [ 65 ]. An interesting aspect observed in a study conducted in Romania in 2020 was that patients who only have NAFLD have lower AST/ALT and fibrosis scores than patients who have concurrent psoriasis [ 83 ]. This demonstrates that the association between NAFLD and psoriasis leads to an unfavorable prognosis in the evolution of liver disease.…”
Section: Correlation Between Psoriasis and Nafldmentioning
confidence: 99%